A identificação de termos de Maçonaria simbólica usando corpora comparáveis - Veiga, Alexandre Trigo (2014)
The present research was developed in order to present an alternative methodology for gathering and identifying terms from a specific area of studies in comparable corpora in Portuguese and English using computer tools designed for linguistic analysis. The selected specific area is Symbolic Freemasonry and the compiled corpora for this study are manuals and rituals used by freemasons during their works that are available in the Internet. The computer tools used for this research are the WordSmith Tools 6.0, the zExtractor and the SketchEngine. The terms identified as a result of this research will provide relevant data for developing a bilingual glossary of Symbolic Freemasonry to aid translators and proof-readers who specialize in masonic works